2011
DOI: 10.1164/rccm.201104-0720oc
|View full text |Cite
|
Sign up to set email alerts
|

Parental Stress Increases the Detrimental Effect of Traffic Exposure on Children's Lung Function

Abstract: Rationale: Emerging evidence indicates that psychosocial stress enhances the effect of traffic exposure on the development of asthma. Objectives: We hypothesized that psychosocial stress would also modify the effect of traffic exposure on lung function deficits. Methods: We studied 1,399 participants in the Southern California Children's Health Study undergoing lung function testing (mean age, 11.2 yr). We used hierarchical mixed models to assess the joint effect of traffic-related air pollution and stress on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 41 publications
2
59
4
2
Order By: Relevance
“…Asthma Outcomes Of the 15 studies that considered the joint contribution of social and environmental exposures in relation to asthma in childhood, four were individual-level prospective cohort studies [12][13][14][15], four were cross-sectional [16][17][18][19], and one was a retrospective cohort study [20] (Table 1). Other approaches included time series [21], case-crossover [22,23], ecologic and spatial [24,25], and econometric [26] designs and analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Asthma Outcomes Of the 15 studies that considered the joint contribution of social and environmental exposures in relation to asthma in childhood, four were individual-level prospective cohort studies [12][13][14][15], four were cross-sectional [16][17][18][19], and one was a retrospective cohort study [20] (Table 1). Other approaches included time series [21], case-crossover [22,23], ecologic and spatial [24,25], and econometric [26] designs and analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian Islam et al, (2011) tentang dampak stres terhadap gangguan saluran pernafasan membuktikan bahwa anak penderita asma yang tumbuh dalam keluarga yang mengalami tingkat stres tinggi mengalami lebih rentan mengalami penurunan fungsi paru akibat paparan polusi udara lebih besar 4.5 kali daripada anak yang dibesarkan dalam keluarga dengan tingkat stres rendah (CI 95 %= -6.5 hingga -2.4).…”
Section: Pengaruh Stres Ibu Terhadap Kejadian Pneumonia Balitaunclassified
“…In a prospective cohort, Shankardass et al reported stronger effects of traffic-related pollution and in utero tobacco smoke on asthma onset among children of parents reporting higher perceived stress [40]. Islam et al found greater impacts of residential and school nitrogen oxides concentrations on forced expiratory volume in 1 s and forced vital capacity among children of parents reporting higher perceived stress, after adjusting for household SEP [41]. We found one cross-sectional study of cardiovascular outcomes; Hicken et al explored self-reported chronic stress, depression, and anxiety as potential effect modifiers of associations between PM 2.5 effects on blood pressure among adults in six US cities, but found no significant effect modification [34‱].…”
Section: Epidemiologic Evidence For Effect Modification By Stress/strmentioning
confidence: 99%